Resin molding and laminate

By depositing modified polymers on the surface of the resin molded body, the problem of insufficient coating performance and adhesion of low-polar resins such as polypropylene in the prior art is solved, and the effects of high adhesion and good recoating performance are achieved, while maintaining mechanical properties and reducing environmental protection impacts.

JP2025040546APending Publication Date: 2025-03-25MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023147404
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to improve the coating performance and adhesion of low-polar resins such as polypropylene without using special equipment for surface treatment, coating adhesive layer or modifying rubber components. At the same time, the environmental impact and mechanical performance of these methods are insufficient.

Method used

Using resin components containing olefin-based modified polymers and thermoplastic resins, a high content surface modified polymer is formed by depositing the modified polymer on the surface of the resin molded body, thereby achieving high adhesion and good recoating performance of the resin molded body.

Benefits of technology

It realizes that the adhesion and coating performance of the resin molded body can be improved without special equipment, while maintaining mechanical properties and reducing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040546000001
    Figure 2025040546000001
Patent Text Reader

Abstract

To provide a resin molding with heightened surface hydrophilicity.SOLUTION: A resin molded body is made of a resin composition (I) containing a modified polymer (A) and a thermoplastic resin (B) (excluding the modified polymer (A)), where the modified polymer (A) has repeat units derived from an olefin-based monomer (a1) and a structure derived from a polyalkylene oxide (a2), and a content ratio of the modified polymer (A) represented by Sc / Ic is greater than 1.0. Sc represents a content of the modified polymer (A) on the surface of the resin molded body, and Ic represents a content of the modified polymer (A) inside the resin molded body. However, the inside of the resin molded body refers to a position located at a distance of 0.375×t (mm) from the surface of the resin molded body in a thickness direction, where t (mm) is the thickness of the resin molded body.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin molded article made of a resin composition containing an olefin-based modified polymer and a thermoplastic resin, and a laminate having the resin molded article. [Background technology]

[0002] Polyolefins such as propylene-based polymers and propylene-α-olefin copolymers are inexpensive and have excellent mechanical properties, heat resistance, chemical resistance, water resistance, etc., and are therefore used in a wide range of fields. However, since the polyolefins do not have polar groups in their molecules, they are generally low polar, making them difficult to coat or adhere to polyolefin substrates, and improvements in coatability and adhesion have been desired. In order to improve coatability and adhesion, various methods have been attempted, such as chemically treating the surface of a polyolefin molded body with a chemical or the like, or oxidizing the surface of the molded body by corona discharge treatment, plasma treatment, flame treatment, etc. However, all of the above treatment methods not only require special equipment, but also do not necessarily improve coatability or adhesion sufficiently.

[0003] Therefore, modified polyolefins such as chlorinated polypropylene, acid-modified propylene-α-olefin copolymer, and acid-modified chlorinated polypropylene have been proposed as a method for imparting good coating properties and adhesion to polyolefins, such as propylene-based polymers, in a relatively simple manner. The modified polyolefins generally have the characteristic that they can be applied to the surface of a polyolefin molded body as a surface treatment agent, adhesive, paint, or the like. The modified polyolefins are usually used in a method of application in the form of a solution dissolved in an organic solvent, or an aqueous dispersion dispersed in water. In terms of hygiene management and environmental load, aqueous dispersions are usually preferably used.

[0004] Patent Document 1 describes an example in which a coating film is formed on a polypropylene substrate by using a dispersion liquid in which a polymer in which a hydrophilic polymer is bound to an acid-modified polyolefin is dispersed in an aqueous medium as a coating material. However, the method described in Patent Document 1 requires a large amount of energy during baking to obtain a dried coating film, and therefore, there remains a problem in terms of environmental load.

[0005] Therefore, a method for modifying the surface of a polyolefin substrate has been proposed. For example, Patent Document 2 proposes a hydrophilicity-imparting agent containing a graft polymer having a hydrophobic polymer block and a hydrophilic polymer block, and describes a polyolefin molded body modified by blending this agent. Patent Document 3 also proposes a resin surface tension modifier containing a block polymer having a hydrophobic polymer block and a hydrophilic polymer block. However, these techniques do not sufficiently hydrophilize the surface. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2007-270122 A [Patent Document 2] JP 2018-44021 A [Patent Document 3] Patent Publication No. 2021-17523 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention aims to provide a resin composition and a molded article which can obtain a resin molded article having a small contact angle and excellent recoatability without requiring surface treatment using special equipment, coating of an adhesive layer, or modification with a rubber component, and which can suppress deterioration of mechanical properties such as elastic modulus by precipitating a modified polymer on the surface. [Means for solving the problem]

[0008] The present invention has the following aspects. [1] A resin molded product comprising a resin composition (I) containing a modified polymer (A) and a thermoplastic resin (B) (excluding the modified polymer (A)), the modified polymer (A) has a repeating unit derived from an olefin monomer (a1) and a structure derived from a polyalkylene oxide (a2); A resin molded article having a content ratio of the modified polymer (A) represented by the following formula (1) of greater than 1.0: Content ratio = Sc / Ic...Formula (1) (In formula (1), Sc represents the content of the modified polymer (A) on the surface of the resin molded body, and Ic represents the content of the modified polymer (A) inside the resin molded body. Here, the inside of the resin molded body refers to a position that is at a distance of 0.375×t (mm) from the surface of the resin molded body in the thickness direction, where t (mm) is the thickness of the resin molded body.) [2] The resin molded article according to [1], wherein the content ratio represented by the formula (1) is greater than 1.1. [3] The resin molded article according to [1] or [2], wherein the modified polymer (A) has a weight average molecular weight of 50,000 or more. [4] The resin molded product according to any one of [1] to [3], wherein the alkylene oxide constituting the polyalkylene oxide (a2) includes at least one of propylene oxide and ethylene oxide. [5] The resin molded product according to any one of [1] to [4], wherein the polyalkylene oxide (a2) is a polyalkylene oxide (a2-1) having a functional group. [6] The resin molded product according to [5], wherein the polyalkylene oxide (a2-1) having a functional group is a polyalkylene oxide having an amino group. [7] A laminate having another layer on at least one surface of a layer made of the resin molded product according to any one of [1] to [6] above. Effect of the Invention

[0009] According to the present invention, by precipitating the modified polymer (A) on the surface, it is possible to obtain a resin molded article that has a small contact angle, excellent recoatability, and can suppress deterioration of mechanical properties such as elastic modulus, without requiring surface treatment using special equipment, coating of an adhesive layer, or modification with a rubber component.

[0010] In the present invention, the surface of the resin molded article is hydrophilized by having a large number of structures derived from polyalkylene oxide present on the surface of the molded article, and the effects of the present invention can be obtained. Furthermore, if the modified polymer (A) has a high molecular weight, it is possible to further suppress the falling off from the surface of the molded article due to bleeding out. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In this specification, the use of "to" indicating a range of values ​​means that the values ​​before and after it are included as the lower limit and upper limit. In this specification, the term "powder" includes primary particles, secondary particles formed by aggregation of primary particles, and aggregates formed by aggregation of these particles. In this specification, "(meth)acrylic" is a general term for acrylic and methacrylic. The number average molecular weight (Mn) and weight average molecular weight (Mw) in this specification are values ​​obtained by measuring with GPC (Gel Permeation Chromatography) using a calibration curve prepared using standard samples with known molecular weights. For example, "polystyrene equivalent" means that the standard sample is polystyrene, and "polypropylene equivalent" means that the standard sample is polypropylene. The molecular weight distribution (Mw / Mn) is the weight average molecular weight (Mw) divided by the number average molecular weight (Mn). In the present specification, compounds with symbols may be simply represented by the symbols. For example, "polyalkylene oxide (a2)" may be represented as "the above (a2)."

[0012] The resin molded article of the present invention comprises a resin composition (I) containing a modified polymer (A) and a thermoplastic resin (B). The components used in the present invention will now be described in order.

[0013] [Modified polymer (A)] The modified polymer (A) used in the present invention has a repeating unit derived from the olefin monomer (a1) and a structure derived from the polyalkylene oxide (a2). The modified polymer (A) in the resin composition (I) may be one type, or two or more types may be used in combination.

[0014] [Olefin monomer (a1)] The olefin monomer (a1) used in the present invention includes α-olefins and cycloolefins. In the modified polymer (A), the molecular structure of the repeating unit derived from the olefin monomer (a1) may be linear, branched, or have a cyclic structure. The olefin monomer (a1) constituting the modified polymer (A) may be one type or two or more types in combination.

[0015] The (a1) preferably has 2 to 7 carbon atoms, and more preferably has 2 to 4 carbon atoms. Specific examples of (a1) include ethylene, propylene, butene-1, pentene-1, hexene-1, heptene-1, octene-1, cyclopentene, cyclohexene, and norbornene.

[0016] In the modified polymer (A), the repeating unit derived from the olefin monomer (a1) preferably contains a repeating unit derived from propylene. When the modified polymer (A) has a repeating unit derived from propylene, the compatibility with polypropylene tends to increase.

[0017] The modified polymer (A) has a structure derived from a polymer having a repeating unit derived from an olefin monomer (a1) (hereinafter, also referred to as "olefin polymer (p-a1)"). The olefin polymer (p-a1) is preferably a propylene homopolymer, a copolymer of propylene and other α-olefins, or a chlorinated polymer thereof, specifically, a propylene homopolymer, an ethylene-propylene copolymer, a propylene-butene copolymer, an ethylene-propylene-butene copolymer, a chlorinated polypropylene, a chlorinated ethylene-propylene copolymer, or a chlorinated propylene-butene copolymer. In terms of improving compatibility with polypropylene, the content of the repeating units derived from propylene relative to the total repeating units of the olefin polymer (p-a1) is preferably 50 mol% or more, more preferably 60 mol% or more, and even more preferably 70 mol% or more. The upper limit is 100 mol% or less. Within this range, the higher the proportion of the repeating units derived from propylene, the higher the compatibility with polypropylene tends to be.

[0018] From the viewpoint of environmental load, the olefin polymer (p-a1) is preferably a chlorine-free olefin polymer, and more preferably a propylene homopolymer, an ethylene-propylene copolymer, a propylene-butene copolymer, or an ethylene-propylene-butene copolymer. The olefin polymer (p-a1) constituting the modified polymer (A) may be one type or a combination of two or more types.

[0019] The melting point of the olefin polymer (p-a1) is preferably 120° C. or lower, more preferably 100° C. or lower, and even more preferably 90° C. or lower. Also, it is preferably 50° C. or higher. The lower the melting point within the above range, the better the adhesion of the topcoat layer (film laminated on the resin molded body) tends to be. The weight average molecular weight (Mw) of the olefin polymer (p-a1) can be determined by measuring with GPC and converting the result using the calibration curve of each polyolefin. The Mw of the olefin polymer (p-a1) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 50,000 or more, and particularly preferably 100,000 or more. Also, it is preferably 500,000 or less, more preferably 300,000 or less. Within the above range, the higher the Mw, the better the mechanical strength of the molded article. Also, the adhesion of the topcoat layer tends to be better. Also, within the above range, the lower the Mw, the lower the melt viscosity, and the easier the mixing during molding. The weight average molecular weight Mw can be measured by GPC using a commercially available GPC device and a solvent such as orthodichlorobenzene, by a conventional method.

[0020] [Unsaturated compound having a reactive group (a3)] The olefin polymer (p-a1) is preferably modified with an unsaturated compound (a3) ​​having a reactive group. The unsaturated compound (a3) ​​having a reactive group used in the present invention has a radical polymerizable unsaturated bond (such as a carbon-carbon double bond) and a reactive group. The (a3) ​​constituting the modified polymer (A) may be one type or two or more types in combination.

[0021] The reactive group of (a3) ​​is preferably at least one selected from the group consisting of a carboxy group and its anhydride, an amino group, an epoxy group, an isocyanate group, a sulfonyl group, and a hydroxyl group. In view of the excellent reactivity of the reactive group, the (a3) ​​is preferably at least one selected from unsaturated compounds having a carboxy group and their anhydrides, such as (meth)acrylic acid, (meth)acrylic anhydride, fumaric acid, fumaric anhydride, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, crotonic acid, and crotonic anhydride.

[0022] The content (graft ratio) of the structure derived from (a3) ​​in the olefin polymer (p-a1) modified with (a3) ​​is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.5% by mass or more. Also, it is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less. Within the above range, the higher the content, the easier it is to introduce a structure derived from polyalkylene oxide, so that the coatability and adhesion of the molded product are improved, and the lower the content, the more the compatibility between the modified polymer (A) and the olefin resin tends to increase.

[0023] [Polyalkylene oxide (a2)] The polyalkylene oxide (a2) used in the present invention is a compound having a repeating unit derived from an alkylene oxide, and examples thereof include polyethylene oxide, polypropylene oxide, polybutylene oxide, and polytetramethylene oxide. These may be used alone or in combination of two or more. It is preferable to include polyethylene oxide and polypropylene oxide in terms of improving the coatability and adhesiveness of the molded article.

[0024] The alkylene oxide constituting the polyalkylene oxide (a2) preferably contains at least one of propylene oxide and ethylene oxide, more preferably contains at least ethylene oxide, and further preferably contains both. When the alkylene oxide constituting the polyalkylene oxide (a2) contains ethylene oxide or propylene oxide, and contains at least ethylene oxide, the ratio of ethylene oxide to the total of ethylene oxide and propylene oxide is preferably 10 mol% or more, more preferably 30 mol%, and even more preferably 60 mol%. The upper limit is 100 mol%, and preferably 90 mol% or less. If it is within the above range, it is possible to impart hydrophilicity when added to a molded product. If the ratio of ethylene oxide is high within the above range, hydrophilicity is easily improved, and if it is low, compatibility with thermoplastic resins tends to be good.

[0025] Examples of the polyalkylene oxide (a2) include polyalkylene oxides (a2-1) having a functional group, polyalkylene oxides (a2-2) having a radically polymerizable group, and polyalkylene oxides (a2-3) having a cyclic structure. The functional group of (a2-1) is preferably one that can react with a reactive group (e.g., a reactive group of an unsaturated compound (a3) ​​having a reactive group described later) of the polymer (p-a1) having a repeating unit derived from the olefin monomer (a1) to form a linking group. Specific examples include a carboxyl group, a dicarboxylic anhydride group, a dicarboxylic anhydride monoester group, a hydroxyl group, an amino group, an epoxy group, an isocyanate group, and the like. Among these, an amino group can react with a carboxyl group, a carboxylic anhydride group, a glycidyl group, or an isocyanate group to form a linking group. The functional group of (a2-1) is preferably an amino group, since it has high reactivity with various reactive groups and can easily bond the olefin polymer (p-a1) with the polyalkylene oxide (a2).

[0026] The amino group may be primary, secondary, or tertiary, but is preferably primary. The functional group of (a2-1) may be one or more, but it is most preferable that it has only one functional group. If there are two or more functional groups, a three-dimensional network structure may form when it is bonded to a polymer (p-a1) having a repeating unit derived from an olefin monomer (a1), which may cause gelation. However, even if it has multiple functional groups, it is sufficient that there is only one highly reactive functional group. For example, a polyalkylene oxide having multiple hydroxyl groups and one amino group that is more reactive than the hydroxyl groups is a preferred example of (a2-1). In this case, reactivity means reactivity with the reactive group of the polymer (p-a1) having a repeating unit derived from an olefin monomer (a1). As a compound having a polyalkylene oxide structure having a primary amino group, Jeffamine M series, D series, ED series, etc. manufactured by Huntsman, which are polyalkylene oxides having primary amino groups, may be used.

[0027] The polystyrene-equivalent Mw of the polyalkylene oxide (a2) measured by GPC is preferably 200 or more, more preferably 300 or more, and even more preferably 500 or more. The upper limit is preferably 100,000 or less, more preferably 10,000 or less, and even more preferably 5,000 or less. The GPC measurement is carried out by a conventionally known method using a commercially available device with THF or the like as a solvent. If the weight average molecular weight (Mw) is equal to or more than the lower limit, the coating property and adhesiveness of the molded product are improved, and if it is equal to or less than the upper limit, the compatibility with thermoplastic resins is improved.

[0028] The polyalkylene oxide (a2) is preferably a hydrophilic compound. In this specification, a hydrophilic compound means a compound which, when dissolved in water at 25° C. at a concentration of 10% by mass, contains no more than 1% by mass of insoluble matter.

[0029] The content of the structure derived from (a2) in the modified polymer (A) is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on the total mass of the modified polymer (A). Also, it is preferably 60% by mass or less, and more preferably 45% by mass or less. If it is more than the lower limit of the above range, hydrophilicity can be imparted to the resin molded product, and if it is less than the upper limit, the handling of the modified polymer (A) powder becomes easy.

[0030] [Other monomers (a4)] The modified polymer (A) may have, in addition to the repeating unit derived from (a1) and the structure derived from (a2), one or more repeating units derived from other monomers (a4) within the range that does not impair the effects of the present invention. Examples of the other monomers (a4) include vinyl acetate, acrylic acid esters, methacrylic acid esters, and aromatic vinyl monomers.

[0031] The content of the repeating units derived from the other monomer (a4) is preferably 10 mol % or less, 5 mol % or less, or 1 mol % or less based on the total repeating units of the modified polymer (A), and may be zero.

[0032] [Method for producing modified polymer (A)] The modified polymer (A) used in the present invention can be produced by the following methods (1) to (4). The copolymer (aa) in the following methods (1) and (2) is a copolymer having a structure derived from the above (a3) ​​in the middle of a main chain having a repeating unit derived from the above (a1), as will be described in detail later. The graft copolymer (aaa) in the following methods (1) and (2) is a graft copolymer (aaa) having a structure derived from the above-mentioned (a3) ​​in a side chain bonded to a main chain having a repeating unit derived from the above-mentioned (a1). Details will be described later. Method (1): A method of reacting the copolymer (aa) or the graft copolymer (aaa) with a polyalkylene oxide (a2-1) having a functional group capable of reacting with the reactive group derived from the (a3). Method (2): A method in which a polyalkylene oxide (A2-2) having a radical polymerizable group is subjected to a graft reaction with an olefin polymer (P-A1), a copolymer (Aa) or a graft copolymer (AAA) using a radical polymerization initiator capable of abstracting hydrogen. Method (3): A method in which a polyalkylene oxide (a2-2) having a radical polymerizable group is copolymerized during the polymerization of an olefin monomer (a1). Method (4): A method of ring-opening polymerization of a polyalkylene oxide (a2-3) having a cyclic alkylene oxide during polymerization of an olefin monomer (a1). The method (1) is preferred in terms of simplicity of synthesis and ease of reaction control.

[0033] The copolymer (aa) is obtained by copolymerizing an olefin monomer (a1) and an unsaturated compound (a3) ​​having a reactive group. The polymerization method for obtaining the copolymer (aa) may be, for example, a radical polymerization method, a cationic polymerization method, an anionic polymerization method, or a coordination polymerization method, and living polymerization may be used in each polymerization method.

[0034] In the case of coordination polymerization, for example, a method of polymerization using a Ziegler-Natta catalyst and a method of polymerization using a single-site catalyst can be mentioned. The method of polymerization using a single-site catalyst is preferable because the molecular weight distribution and stereoregularity distribution can be made sharp by designing the ligand. As the single-site catalyst, for example, a metallocene catalyst or a Brookhart catalyst can be used. As the metallocene catalyst, a suitable catalyst such as C1 symmetric type, C2 symmetric type, C2V symmetric type, or CS symmetric type can be selected according to the stereoregularity of the polyolefin to be polymerized.

[0035] The polymerization form when producing the copolymer (aa) can be any of solution polymerization, slurry polymerization, bulk polymerization, gas phase polymerization, etc. Examples of the solvent in the case of solution polymerization and slurry polymerization include aromatic hydrocarbons such as toluene and xylene; aliphatic hydrocarbons such as hexane, heptane, octane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; halogenated hydrocarbons, esters, ketones, ethers, etc. In terms of easily dissolving the copolymer (aa), aromatic hydrocarbons, aliphatic hydrocarbons, and alicyclic hydrocarbons are preferred, and toluene, xylene, heptane, and cyclohexane are more preferred. These may be used alone or in combination of two or more.

[0036] The graft polymer (aaa) can be obtained by grafting the unsaturated group of the unsaturated compound (a3) ​​having a reactive group to the main chain of the olefin polymer (p-a1) having a repeating unit derived from the olefin monomer (a1). The graft reaction method is not particularly limited, but examples include a method of dissolving the (p-a1) and the (a3) ​​in a solvent and grafting the same, a method of melting and heating and stirring the same in a solvent and grafting the same, and a method of heating and kneading the same in an extruder and grafting the same. When the copolymer (aa) is dissolved in a solvent to produce the copolymer, the solvents exemplified in the examples can be used in the same manner.

[0037] In the above graft reaction, a radical polymerization initiator can be used. The radical polymerization initiator can be appropriately selected from initiators used in normal radical polymerization reactions, and examples thereof include organic peroxides and azonitriles. Examples of the organic peroxides include peroxyketals such as di(t-butylperoxy)cyclohexane; hydroperoxides such as cumene hydroperoxide; dialkyl peroxides such as di(t-butyl)peroxide; diacyl peroxides such as benzoyl peroxide; and peroxyesters such as t-butylperoxyisopropyl monocarbonate. Examples of the azonitriles include azobisbutyronitrile and azobisisopropylnitrile. Benzoyl peroxide and t-butylperoxyisopropyl monocarbonate are preferred because they have a strong hydrogen abstracting power and are excellent in graft reaction. These may be used alone or in combination of two or more.

[0038] The ratio of the radical polymerization initiator to all repeating units of the graft copolymer (aaa) is preferably 1:100 to 2:1 (molar ratio), more preferably 1:20 to 1:1 (molar ratio). Within the above range, bonding between the graft copolymers can be suppressed. The reaction temperature is preferably 50°C or higher, more preferably 80 to 200°C. Within the above range, the graft reaction proceeds due to the hydrogen abstraction power of the radical polymerization initiator. The reaction time is usually about 2 to 20 hours. In this specification, the number of moles of all repeating units of the graft copolymer (aaa) is the sum of the number of moles of the units derived from (a1) and the number of moles of the units derived from (a3).

[0039] When producing the graft polymer (aaa), the copolymer (aa) may be used as the olefin polymer (p-a1) having a repeating unit derived from the olefin monomer (a1). Examples of the graft polymer (aaa) include the following: Maleic anhydride-modified polypropylene, which is obtained by grafting maleic anhydride onto polypropylene, and its chlorinated products; Maleic anhydride-modified ethylene-propylene copolymers obtained by grafting maleic anhydride onto ethylene-propylene copolymers and their chlorinated products; Maleic anhydride-modified propylene-butene copolymers obtained by grafting maleic anhydride onto propylene-butene copolymers and their chlorinated products; Acrylic acid modified polypropylene obtained by grafting acrylic acid onto polypropylene and its chlorinated products; Acrylic acid-modified ethylene-propylene copolymer obtained by grafting acrylic acid onto ethylene-propylene copolymer and its chlorinated product; Acrylic acid modified propylene-butene copolymers obtained by grafting acrylic acid onto propylene-butene copolymers, and their chlorinated products. The graft polymer (aaa) may be used alone or in combination of two or more kinds.

[0040] In the method (1), the step of reacting the copolymer (aa) or the graft copolymer (aaa) with the (a2-1) to obtain the modified polymer (A) is not particularly limited, but examples thereof include a method of dissolving the copolymer (aa) or the graft copolymer (aaa) in a solvent and reacting it with the (a2-1), a method of melting and heating and stirring the copolymer without a solvent and reacting it, a method of heating and kneading the copolymer in an extruder and reacting it, etc. When dissolving the copolymer in a solvent to produce the modified polymer (A), the solvents exemplified for the production of the copolymer (aa) can be used in the same way.

[0041] The Mw (polystyrene equivalent) of the copolymer (aa) or the graft copolymer (aaa) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 50,000 or more, and particularly preferably 100,000 or more. Also, it is preferably 500,000 or less, more preferably 300,000 or less. Within the above range, the larger the weight average molecular weight Mw, the higher the rigidity of the resin molded product tends to be. Also, within the above range, the smaller the weight average molecular weight Mw, the higher the compatibility with thermoplastic resins tends to be.

[0042] In the method (1), a modified polymer (A) having a linking group formed by a reaction between a reactive group derived from the (a3) ​​present in the copolymer (aa) or the graft copolymer (aaa) and a functional group of the polyalkylene oxide (a2-1) is obtained. For example, when the copolymer (aa) is used, a modified polymer (A) is obtained which has a main chain having a repeating unit derived from the (a1) and a structure derived from the (a3), and a side chain having a structure derived from the (a2-1), and the side chain is bonded to the structure derived from the (a3) ​​via the linking group. In addition, when the graft copolymer (aaa) is used, a modified polymer (A) is obtained which has a main chain having a repeating unit derived from the (a1) and a side chain having a structure derived from the (a3) ​​and a structure derived from the (a2-1), in which the structure derived from the (a3) ​​is bonded to the main chain and the structure derived from the (a2-1) is bonded to the structure derived from the (a3) ​​via the linking group.

[0043] Examples of the linking group include an amide bond formed by a reaction between a carboxy group or an acid anhydride group, which is a reactive group in the (a3), and an amino group, which is a functional group in the (a2-1).

[0044] [Physical form of modified polymer (A)] The physical form of the modified polymer (A) used in the present invention may be powder, particles, pellets, or lumps. Specific examples include suspension polymerization particles of the modified polymer (A), particles obtained by pulverizing the modified polymer (A) into lumps, particles obtained by melting the modified polymer (A) and pelletizing it, powder obtained by filtering and / or drying a dispersion of the modified polymer (A), and powder obtained by dissolving or melting the modified polymer (A) in a solvent, precipitating it in a poor solvent, and then filtering and / or drying it. In terms of good mixability when used in a molded product and improved strength and appearance, a method that obtains a dried powder state is preferred, and a method that obtains a powder by drying a dispersion of the modified polymer (A) by spray drying is more preferred.

[0045] The average particle size of the modified polymer (A) powder is preferably more than 3.2 μm and not more than 100 μm, more preferably 3.5 μm or more, and even more preferably 5 μm or more, and more preferably 50 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. When the average particle size is equal to or less than the upper limit, the coatability and adhesiveness of the molded article are easily improved, whereas when the average particle size is equal to or more than the lower limit, the handleability when used in the production of a molded article is easily improved. In this specification, the average particle size of a powder is the median size at 50% of the cumulative size in the particle size distribution based on the number of particles measured by an image particle size distribution measurement method.

[0046] [Physical properties of modified polymer (A)] The weight average molecular weight Mw of the modified polymer (A) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 50,000 or more, and particularly preferably 100,000 or more. Also, it is preferably 500,000 or less, more preferably 300,000 or less. Within the above range, the higher the weight average molecular weight (Mw), the higher the rigidity of the resin molded product tends to be. Also, within the above range, the lower the weight average molecular weight (Mw), the higher the compatibility with thermoplastic resins tends to be.

[0047] The melting point Tm of the modified polymer (A) is preferably 120° C. or lower, more preferably 100° C. or lower, and even more preferably 90° C. or lower. The melting point Tm of the modified polymer (A) is preferably 50° C. or higher. Within the above range, the higher the melting point, the higher the rigidity of the resin molded article tends to be, and the lower the melting point, the higher the paintability of the resin molded article and the adhesion to the topcoat layer tend to be.

[0048] The powder of the modified polymer (A) may contain volatile components, such as residual solvents such as water, alcohol, and organic solvents, and unreacted monomers. The volatile content is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, based on the total mass of the modified polymer (A) powder. If the volatile content is within the above range, the appearance of the molded article is improved when used. In this specification, the volatile content means the value calculated from the weight loss when 1.0 g of a sample is heated at 180°C using an infrared moisture meter and the weight change is within 0.05% in 60 seconds.

[0049] [Thermoplastic resin (B)] The thermoplastic resin (B) is not particularly limited as long as it is a thermoplastic resin other than the modified polymer (A). The thermoplastic resin (B) in the resin composition (I) may be one type or two or more types in combination. Examples of the thermoplastic resin (B) include polyolefin polymers (B1) such as polypropylene (PP), polyethylene (PE), ethylene / propylene copolymers, and cycloolefin polymers (COP); fluororesins (B2) such as polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymers (ETFE), perfluoroalkoxyalkanes (copolymers of tetrafluoroethylene (C2F4) and perfluoroalkoxyethylene (PFA), and polyvinylidene fluoride (PVDF); and polystyrene resins (B3) such as polystyrene (PS) and impact-resistant polystyrene, including copolymers having as constituent units vinyl group-containing aromatic hydrocarbons alone and vinyl group-containing aromatic hydrocarbons and one or more selected from the group consisting of butadiene. The olefin polymer (B1) is preferred in view of the mechanical properties, adhesion and wettability of the molded product and the durability of these properties. Among these, polypropylene homopolymers, random copolymers and block copolymers are preferred in terms of cost, mechanical strength and the like.

[0050] When the modified polymer (A) and the thermoplastic resin (B) coexisting in the resin composition (I) both have repeating units derived from the olefin monomer (a1), the types of the repeating units may be the same or different.

[0051] As described later, in the resin molded article of the present invention, the modified polymer (A) is unevenly distributed on the surface rather than inside the resin molded article. In view of the tendency of uneven distribution of the modified polymer (A), the thermoplastic resin (B) is preferably a polyolefin polymer (B1) containing random polypropylene. For example, the proportion of random polypropylene relative to the total mass of the polyolefin polymer (B1) is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more. It may be 100% by mass.

[0052] [Other components (C)] The resin composition (I) used in the present invention may contain other components (C) in addition to the modified polymer (A) and the thermoplastic resin (B).

[0053] Furthermore, as the other component (C), a resin other than the modified polymer (A) and the thermoplastic resin (B) may be contained within a range that does not impair the effects of the present invention. Examples of the other resins include olefin resins other than the modified polymer (A) and the thermoplastic resin (B), acrylic resins, urethane resins, polyester resins, polycarbonate resins, polystyrene resins, vinyl acetate resins, vinyl chloride resins, vinylidene chloride resins, styrene-butadiene resins, butadiene resins, poly(meth)acrylonitrile resins, (meth)acrylamide resins, nylon resins, phenolic resins, silicone resins, and epoxy resins. Other components (C) may include elastomer components such as EPR, EPDM, and hydrogenated styrene-based elastomers, dispersants, plasticizers, solvents, crosslinking agents, lubricants, antioxidants, UV absorbers, light stabilizers, fillers, antistatic agents, lubricants, antiblocking agents, colorants such as dyes and pigments, modifying resins, etc. These may be one type or two or more types, and may or may not be mixed in advance with the thermoplastic resin (B).

[0054] [Resin composition (I)] The resin composition (I) contains a modified polymer (A) and a thermoplastic resin (B), and may further contain another component (C). The content of the modified polymer (A) is preferably 0.1 to 70% by mass, more preferably 1 to 50% by mass, and even more preferably 2 to 30% by mass, based on the total mass of the resin composition (I).Within the above range, the higher the content, the better the paintability and adhesiveness of the molded product.In addition, the lower the content, the higher the rigidity of the molded product.

[0055] The content of the thermoplastic resin (B) is preferably 20 to 70 mass%, more preferably 30 to 65 mass%, and even more preferably 40 to 60 mass%, based on the total mass of the resin composition (I).Within the above range, the higher the content, the better the mechanical properties.In addition, the lower the content, the better the recoatability.

[0056] In the resin composition (I), the mass ratio of "modified polymer (A) / thermoplastic resin (B)" is preferably 50 / 50 to 1 / 99, more preferably 20 / 80 to 2 / 98. If the content of the modified polymer (A) is within the above range, the higher the content, the better the recoatability, and the lower the content, the better the rigidity of the molded article tends to be.

[0057] The total content of the other components (C) is preferably 40% by mass or less, more preferably 30% by mass or less, based on the total mass of the resin composition (I). The lower limit may be zero. Various components (C) may be added depending on the required physical properties within a range that does not impair the effects of the present invention.

[0058] The resin composition (I) used in the present invention may contain volatile components, such as residual solvents such as water, alcohol, and organic solvents, unreacted monomers, and decomposition products resulting from the molding process. The volatile content is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less, based on the total mass of the resin composition (I). If the volatile content is within the above range, the appearance of the molded article when used is improved.

[0059] [Resin molding] The resin molded article of the present invention is made of the resin composition (I). The shape of the resin molded article is not limited in any way, and may be, for example, a film, a sheet, a plate, or a part having a complex shape.

[0060] The resin molded article of the present invention has a different content of the modified polymer (A) between the surface and the inside. The modified polymer (A) is unevenly distributed on the surface of the resin molded article compared to the inside. Specifically, in the resin molded product of the present invention, the content ratio (Sc / Ic) of the modified polymer (A) represented by the following formula (1) is greater than 1.0, preferably greater than 1.1, and more preferably greater than 1.2. The larger the content ratio (Sc / Ic), the smaller the water contact angle of the surface of the resin molded product tends to be. The upper limit of the content ratio (Sc / Ic) is not particularly limited, but is preferably 5 or less in order to maintain the surface hardness.

[0061] Content ratio = Sc / Ic...Formula (1) (In formula (1), Sc represents the content of the modified polymer (A) on the surface of the resin molded body, and Ic represents the content of the modified polymer (A) inside the resin molded body. Here, the inside of the resin molded body refers to a position that is at a distance of 0.375×t (mm) from the surface of the resin molded body in the thickness direction, where t (mm) is the thickness of the resin molded body.)

[0062] The content of the modified polymer (A) on the surface or inside of the resin molded product is obtained by calculating the abundance ratio [α] of the modified polymer (A) in the resin molded product by Raman spectroscopy. Specifically, a Raman microscope (Nanophoton product name "RAMANtouch") is used to obtain spectra of the surface and inside of the resin molded product. Measurements of the inside of a resin molding are carried out as follows. After focusing the laser on the surface of the molding, the distance between the objective lens and the resin molding is brought 0.50 mm closer, and the focal position is set inside the resin molding for measurement. When focusing the laser inside the resin molding, the distance the laser focus moves within the resin molding can be roughly calculated as the product of the movement distance of the sample z-stage and the refractive index of the sample at the measurement wavelength (excitation wavelength). The refractive index of the resin molding is, for example, 1.5. In this specification, the inside of the molded body refers to a point that is 0.375×t (mm) from the surface of the resin molded body in the thickness direction, where t (mm) is the thickness of the resin molded body.

[0063] The measurement conditions for Raman spectroscopy are set as follows: excitation wavelength 532 nm, objective lens 5x, excitation light intensity 6.25 mW, exposure time 10 seconds, number of integrations 1, diffraction grating 300 gr / min. The analysis method is to apply formula (X1) to the spectrum (X) of the resin molded body obtained from the resin molded body by the CLS (Classical Least Squares) method and the spectra obtained from the modified polymer (A) and thermoplastic resin (B) to calculate the component ratio. Using the analysis software RAMAN Viewer attached to the device, the existence ratios α and β are calculated so that the residual R is minimized, assuming that the mixed spectrum X is the linear sum of spectra A and B. If other components (C) are included in addition to the modified polymer (A) and thermoplastic resin (B), the component ratio of the modified polymer (A) is calculated taking them into account. Note that (Σ) indicates the wavelength range used in the calculation. X(Σ)=αA(Σ)+βB(Σ)+γC(Σ)+R(Σ)...Equation (X1) X: Spectral vector of a resin molding made of a resin composition [I] containing a modified polymer (A) and a thermoplastic resin (B) A: Spectral vector of modified polymer (A) B: Spectral vector of thermoplastic resin (B) C: Spectral vector of other components (C) α: Abundance ratio of modified polymer (A) β: Abundance ratio of thermoplastic resin (B) γ: Abundance ratio of other components (C) R: vector of residuals Σ: Applicable wavelength range

[0064] The wavelength range to be analyzed is not limited in any way, but it is preferable to include a wavelength range in which a characteristic peak of each component is observed.

[0065] The modified polymer (A), the thermoplastic resin (B), and the other components (C) may be mixed independently to form a molded product, or a molded product may be formed by mixing some of them in advance. When a molded product is formed by mixing some of them in advance, the spectrum of each component may be measured and used for analysis, as shown in formula (X2). X(Σ)=αA(Σ)+θQ(Σ)+R(Σ)...Formula (X2) X: Spectral vector of a resin molding made of a resin composition [I] containing a modified polymer (A) and a thermoplastic resin (B) A: Spectral vector of modified polymer (A) Q: Spectrum of a mixture of thermoplastic resin (B) and other components (C) α: Abundance ratio of modified polymer (A) θ: Ratio of thermoplastic resin (B) and other components (C) in the mixture R: vector of residuals Σ: Applicable wavelength range

[0066] [Method for producing resin composition (I) and resin molded product] The resin composition (I) can be produced by mixing the modified polymer (A), the thermoplastic resin (B), and, if necessary, other components (C). For example, a method can be used in which a powdered modified polymer (A) and a pellet-shaped thermoplastic resin (B) are premixed without being melted, then kneaded while being heated and melted to obtain a kneaded product having fluidity, and the kneaded product obtained is molded to obtain a resin molded body. As the production apparatus, a twin-screw extruder, an injection molding machine, a blow molding machine, an inflation molding machine, a T-die molding machine, etc. can be used. An injection molding machine is particularly preferred because it is easy to control the external force and environment during molding and it facilitates precipitation of the modified polymer (A). The content ratio (Sc / Ic) can be adjusted by adjusting the molding conditions. For example, increasing the cylinder temperature during injection molding tends to increase the content ratio (Sc / Ic), and increasing the mold temperature during injection molding to increase the injection speed tends to increase the content ratio (Sc / Ic). As injection molding conditions, for example, the cylinder temperature is preferably 150 to 250°C, more preferably 160 to 200°C. If the cylinder temperature is higher than 250°C, a large amount of decomposition products are generated and the resin turns yellow. Furthermore, the mold temperature is preferably 40 to 90°C, more preferably 50°C or higher, and more preferably 60°C or higher. If the mold temperature is higher than 90°C, sink marks and the like may occur, resulting in molding defects. Within the above range, the content ratio (Sc / Ic) is easily adjusted to be greater than 1.0.

[0067] The water contact angle of the surface of the resin molded article of the present invention is preferably 90° or less, more preferably 40° or more and less than 90°, and even more preferably 45° or more and 85° or less. When the water contact angle is within the above range, the paintability and adhesiveness of the surface of the resin molded article tend to be good.

[0068] Applications of the resin molded article of the present invention include, for example, automobile interior and exterior parts, food containers, medical containers, components of furniture, components of electrical appliances, toys, and civil engineering and construction materials.

[0069] [Laminate] The laminate of the present invention has another layer on at least one surface of the layer made of a resin molded product. The layer made of the resin molded body may have other layers on both the front and back surfaces. Another layer may be laminated on the entire surface of the layer made of the resin molded body, or on a part of the surface. Examples of the other layers include coating layers such as an adhesive layer, an ink layer, and a hard coat layer. The other layer may be a single layer or a laminate of two or more layers.

[0070] An example of the laminate of the present invention is a coated product in which the surface of a substrate body made of a resin molded product is coated with a paint to laminate one or more coating layers. In a coated article, the thickness of one coating layer (a layer made of one type of paint) is, for example, preferably 0.1 to 20 μm, and more preferably 1 to 10 μm. The paint is not limited in any way, but from the viewpoint of environmental load, a water-based paint in which a resin component is dissolved or dispersed in a medium containing water is preferred. In addition to the resin component, the paint may contain a pigment and / or additional components as required depending on the required function.

[0071] In the laminate of the present invention, the modified polymer (A) is unevenly distributed on the surface of the resin molded product, and thus the polar group (structure derived from polyalkylene oxide) is also unevenly distributed on the surface of the resin molded product, which improves the recoatability of the resin molded product and also provides excellent adhesion to the topcoat layer. EXAMPLES

[0072] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited thereto. In the examples, "parts" refers to "parts by mass." Measurements and evaluations were performed by the methods shown below.

[0073] [Content of maleic anhydride-derived structure in polymer (graft ratio)] 200 mg of the polymer to be measured and 4800 mg of chloroform were placed in a 10 mL sample bottle and heated at 50°C for 30 minutes to completely dissolve the polymer solution. Chloroform was placed in a liquid cell made of NaCl and with an optical path length of 0.5 mm to serve as a background. Next, the polymer solution was placed in the liquid cell, and an infrared absorption spectrum was measured with an infrared spectrophotometer (product name "FT-IR460plus" by JASCO Corporation) at an accumulation count of 32 times. The graft ratio of maleic anhydride was calculated by measuring a solution of maleic anhydride dissolved in chloroform and creating a calibration curve. -1 Nearby maximum peak, 1750-1813 cm -1 ) based on a separately prepared calibration curve, the content of maleic anhydride in the polymer was calculated, and this was taken as the graft rate (wt %) of maleic anhydride.

[0074] [Measurement of the average particle size of modified polymer (A) powder] The modified polymer (A) powder was used as a sample, and the particle size distribution based on the number was measured using an image type particle size distribution measuring device manufactured by Malvern Panalytical Co., Ltd. The median diameter at the cumulative 50% in the obtained particle size distribution was taken as the average particle size of the modified polymer (A) powder.

[0075] [Measurement of water contact angle of resin molded body] Using an automatic contact angle meter (Kyowa Interface Science Co., Ltd. product name "DM500"), the contact angle of the surface of the resin molded body to be measured was measured by the drop method. The drop was 1 μL of water, and the static contact angle was measured 2 seconds after the drop landed.

[0076] [Melt point measurement] The object to be measured was dried at 40°C under reduced pressure for 6 hours to prepare a sample. 5±1 mg of the sample was placed in an aluminum pan, covered with an aluminum lid, and measured using an empty aluminum container as a reference. The temperature was raised to 200°C at a rate of 10°C / min using a differential scanning calorimeter (EXSTAR6000, manufactured by Seiko Instruments Inc.). After holding at the same temperature for 5 minutes, it was cooled at a rate of 10°C / min, and the amount of heat was detected at 0°C to 0°C at 0.5 second intervals. After holding at the same temperature for 1 minute, it was raised to 200°C at a rate of 10°C / min, and the amount of heat was detected at 0.5 second intervals. The peak top temperature of the crystal melting peak in the final heating process was taken as the melting point [Tm] (°C).

[0077] [Content ratio of modified polymer (A) in resin molded product] A resin molded article having a thickness of 2 mm was used as the measurement subject, and the abundance ratio [α] of the modified polymer (A) was calculated by Raman spectroscopy to obtain the content of the modified polymer (A). Specifically, a microscopic Raman spectrometer (Nanophoton product name "RAMANtouch") was used to obtain spectra of the surface and interior of the resin molded body. Measurements of the inside of the resin molding were carried out as follows. After focusing the laser on the surface of the resin molding, the distance between the objective lens and the resin molding was brought 0.50 mm closer, and the focal position was moved inside the molding for measurement. When focusing the laser inside the resin molding, the distance the laser focal point moved in the resin molding can be roughly calculated by the product of the movement distance of the sample z-stage and the refractive index of the sample. Therefore, the inside of the resin molding here was defined as a position 0.75 mm inward from the surface of the resin molding. (However, the refractive index of the resin molding was set to 1.5.) The measurement conditions for Raman spectroscopy were set as follows: excitation wavelength 532 nm, objective lens 5x, excitation light intensity 6.25 mW, exposure time 10 seconds, number of integrations 1, and diffraction grating 300 gr / min. The analysis method was to apply formula (X3) to the spectrum (A) and spectrum (B) obtained from the modified polymer (A) and thermoplastic resin (B) by the CLS (Classical Least Squares) method, and the spectrum (X) obtained from a resin molded product made of a resin composition [I] containing the modified polymer (A) and the thermoplastic resin (B) to calculate the component ratio. Using the analysis software RAMAN Viewer attached to the device, the mixed spectrum X was assumed to be the linear sum of the known spectra A and B, and the component ratio was calculated from the wavenumber of 350 to 3200 cm. -1 The abundance ratios α and β were calculated so that the residual error R was smallest in this wavelength range. X(Σ)=αA(Σ)+βB(Σ)+R(Σ)...Equation (X3) X: Spectral vector of a resin molding made of a resin composition [I] containing a modified polymer (A) and a thermoplastic resin (B) A: Spectral vector of modified polymer (A) B: Spectral vector of thermoplastic resin (B) α: Abundance ratio of modified polymer (A) β: Abundance ratio of thermoplastic resin (B) R: vector of residuals Σ: Applicable wavelength range Furthermore, the content (Sc or Ic, unit: %) of the modified polymer (A) in the resin molded product was calculated by the following formula (Y). (Sc or Ic)=α / (α+β)×100...Formula (Y)

[0078] [Production Example 1: Production of Graft Copolymer (aaa)] In this example, the (a1) and the (a3) ​​were reacted in the presence of a radical polymerization initiator to produce a maleic anhydride-modified propylene-butene copolymer, which is a graft copolymer (aaa). First, 200 kg of a propylene-butene copolymer polymerized by a metallocene catalyst (Mitsui Chemicals product name "Tafmer (registered trademark) XM-7070", melting point 75 ° C., propylene content 74 mol%, weight average molecular weight [Mw] 250,000 (polypropylene equivalent), molecular weight distribution [Mw / Mn] 2.2) and 5 kg of maleic anhydride were dry blended in a super mixer. Then, using a twin-screw extruder (Japan Steel Works product name "TEX54αII"), t-butylperoxyisopropyl monocarbonate (NOF Corp. product name "Perbutyl I") was fed in the middle with a liquid addition pump so that 1 part by mass was obtained for 100 parts by mass of the propylene-butene copolymer, and the mixture was kneaded under the conditions of a cylinder temperature of 200 ° C. in the kneading section, a screw rotation speed of 125 rpm, and a discharge rate of 80 kg / hour to obtain a pellet-shaped maleic anhydride-modified propylene-butene copolymer. The maleic anhydride-modified propylene-butene copolymer thus obtained was found to have a maleic anhydride-derived structure content (graft ratio) of 1% by mass as measured by the above-mentioned method, a weight average molecular weight (polystyrene equivalent) [Mw] of 160,000, and a number average molecular weight [Mn] of 80,000.

[0079] [Production Example 2: Production of modified polymer (A)] In this example, the graft copolymer (aaa) and the (p-a1) were further reacted with the (a3) ​​in the presence of a radical polymerization initiator to improve the maleic acid modification rate, and then the (a2-1) was reacted to produce the modified polymer (A). First, the inside of a glass flask equipped with a reflux condenser, a thermometer, and a stirrer was replaced with nitrogen gas, and 50 g of the maleic anhydride-modified propylene-butene copolymer obtained in Production Example 1 and 50 g of the same propylene-butene copolymer as Production Example 1 were dissolved in 120 g of toluene, and 1.0 g of maleic anhydride and 0.5 g of t-butylperoxyisopropyl monocarbonate (NOF Corp. product name "Perbutyl I") were added and reacted at 110°C for 7 hours. The reaction liquid was then cooled to 70°C. 30 g of methoxypoly(oxyethylene / oxypropylene)-2-propylamine (Huntsman Corp. product name "Jeffamine M-1000") was added to 50 g of 2-propanol, which was then dropped into the reaction liquid and reacted at 70°C for 1 hour. The temperature of the reaction solution was then kept at 45°C, and the mixture was heated and stirred, and 300 g of water was added dropwise while reducing the pressure inside the system, and toluene and 2-propanol were distilled off under reduced pressure until the polymer concentration reached 30% by mass, thereby obtaining a dispersion in which the modified polymer (A) was dispersed in water. The resulting dispersion was milky white, and the average particle size (cumulant) of the dispersoid was 110 nm. The content of the structure derived from (a2) was 23 mass % based on the total mass of the modified polymer (A).

[0080] [Production Example 3: Production of modified polymer (A) powder] The dispersion obtained in Production Example 2 was spray-dried to powder using a spray dryer (Price product name "TR160 type", two-fluid nozzle type) under conditions of a spray pressure of 0.3 MPa, an inlet temperature of 100°C, an outlet temperature of 37°C, and a coating rate of 5.9 kg / hr. The obtained modified polymer (A) powder had a number-average particle size of 6.3 μm (standard deviation of 4.4 μm), a volatile content of 3 mass%, a weight-average molecular weight (polystyrene equivalent) of 200,000, and a melting point of 70°C.

[0081] [Example 1: Production of resin molded body 1] In this example, the modified polymer (A) and the thermoplastic resin (B) were mixed and injection molded to produce a resin molded article made of the resin composition (I). First, 30 parts of the modified polymer (A) powder obtained in Production Example 3 and 70 parts of polypropylene (Japan Polypropylene product name "WintecWMG03", random polypropylene, pellet form), which is a thermoplastic resin, were dry blended in a super mixer, and then mixed using a twin-screw extruder (Technovel product name "KZW15"), and then molded into a plate (80 mm x 40 mm x 2 mm) using an injection molding machine (Sumitomo Heavy Industries product name "SE18") to obtain resin molded body 1. The mixing conditions in the twin-screw extruder were a cylinder temperature of 180° C. and a screw rotation speed of 125 rpm. The molding conditions in the injection molding machine were a cylinder temperature of 200° C., a mold temperature of 80° C., and an injection speed of 150 mm / s. The content Sc of the modified polymer (A) on the surface of the resin molded body and the content Ic of the modified polymer (A) inside the resin molded body were measured by the above-mentioned method, and the value of Sc / Ic was obtained. The water contact angle of the resin molded body was also measured by the above-mentioned method. These results are shown in Table 1 (hereinafter the same).

[0082] [Example 2: Production of resin molded body 2] A resin molded product 2 was obtained in the same manner as in Example 1, except that the molding conditions in the injection molding machine were changed as shown in Table 1.

[0083] [Example 3: Production of resin molded body 3] Resin molded body 3 was obtained in the same manner as in Example 1, except that the molding conditions in the injection molding machine were changed as shown in Table 1.

[0084] [Example 4: Production of resin molded body 4] A resin molded product 4 was obtained in the same manner as in Example 1, except that the modified polymer (A) was not used and the graft copolymer (aaa) obtained in Production Example 1 was used instead. In this example, the content of the graft copolymer (aaa) on the surface of the resin molded article was designated as Sc, and the content of the graft copolymer (aaa) inside the resin molded article was designated as Ic.

[0085] [Table 1]

[0086] As shown in the results in Table 1, the resin molded articles of Examples 1 to 3 using the modified polymer (A) had larger Sc / Ic values ​​than Example 4 using the graft copolymer (aaa). This shows that the modified polymer (A) is more likely to be unevenly distributed on the surface of the resin molded article in Examples 1 to 3 than in Example 4. Comparing Examples 1 to 3, the water contact angle decreased and hydrophilicity increased as the Sc / Ic value increased. In Examples 1 and 2, where the Sc / Ic value was greater than 1.0, the water contact angle of the resin molded article was sufficiently small, and in Example 1, where the Sc / Ic value was greater than 1.1, the water contact angle of the resin molded article was even smaller.

Claims

1. A resin molded product made of a resin composition (I) containing a modified polymer (A) and a thermoplastic resin (B) (excluding the modified polymer (A)), The modified polymer (A) has a repeating unit derived from an olefin monomer (a1) and a structure derived from a polyalkylene oxide (a2), A resin molded article having a content ratio of the modified polymer (A) represented by the following formula (1) of greater than 1.0: Content ratio = Sc / Ic...Formula (1) (In formula (1), Sc represents the content of the modified polymer (A) on the surface of the resin molded body, and Ic represents the content of the modified polymer (A) inside the resin molded body. Here, the inside of the resin molded body refers to a position that is at a distance of 0.375×t (mm) from the surface of the resin molded body in the thickness direction, where t (mm) is the thickness of the resin molded body.)

2. The resin molded article according to claim 1 , wherein the content ratio represented by the formula (1) is greater than 1.

1.

3. 3. The resin molded article according to claim 1, wherein the modified polymer (A) has a weight average molecular weight of 50,000 or more.

4. 3. The resin molded article according to claim 1, wherein the alkylene oxide constituting the polyalkylene oxide (a2) contains at least one of propylene oxide and ethylene oxide.

5. 3. The resin molded article according to claim 1, wherein the polyalkylene oxide (a2) is a polyalkylene oxide (a2-1) having a functional group.

6. 6. The resin molded article according to claim 5, wherein the polyalkylene oxide (a2-1) having a functional group is a polyalkylene oxide having an amino group.

7. A laminate comprising a layer of the resin molded article according to claim 1 or 2 and another layer on at least one surface of the layer.

Citation Information

Patent Citations

  • Resin dispersion, coating and laminate, and manufacturing method for the same

    JP2007270122A

  • Hydrophilicity imparting agent

    JP2018044021A

  • Resin surface tension adjuster

    JP2021017523A